International Public Policy and Management: Policy Learning Beyond Regional Cultural, and Political Boundaries (Marcel Dekker, 2004)
"This reference explores new patterns and advances in the global integration of policies that result from an ever-increasing pace of shared knowledge, regulations, and norms in countries around the globe." "A study of economic, state, social, and international restructuring, this guide analyzes the experiences of various nations undergoing policy dilemmas in areas including telecommunications, healthcare, commerce, and urban affairs."